Delineation of Water Logging and Salinity for Salvaging Built Environment - Rao Atif,; Mohammed Raza Mehdi ,; Sheeba Afsar, (Journal of Basic & Applied Sciences, 2021)
Millions of acres of splendidly productive land and valuable infrastructure are deteriorated continuously. The reason for such deterioration in majority of areas is mainly due to water logging and salinity. Rise of water table level and the dearth of drainage and lack of continuous monitoring and timely remedial measures, extended the circle of devastation to historical heritage and precious archeological sites as well. Mohenjo-Daro has been selected for this study, it has global significance but due to water logging and salinity, it is in danger of total destruction. The archeological buildings and other infrastructure and land in its environs are being gradually eroded by the capillary rise of saline ground the intensity of which constitutes a serious threat. For delineating and periodic monitoring of the salinity and waterlogging and to effectively implement the appropriate remedies, use of the latest technologies is essential. In this study the remote sensing technologies are used to address this issue with the help of Soil investigation parameters mainly EC and pH. The aftermaths of this study would provide a methodological framework along with practical application in delineation saline areas using satellite technology. The final value-added products of this research would be useful for all interested stakeholders including conservationists, environmentalists, archeologists, planners and decision-makers at various levels. The international community at large would be the beneficiary of this study since Mohenjo-Daro is the heritage of entire mankind.